Zoning System Policy Model in Accepting New Students in Indonesia - Kosasih, Fitriyani; Rochmani, Rochmani; Folia, Roli Cahya (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2023)
This study aims to see and describe the implementation of the Van Meter and Van Horn policy models. The results of this study are: 1) Implementation and communication activities between policy implementing organizations have been implemented, but the results have not been optimal, 2) The characters of Public Senior High School 2 Ciamis as implementers have understood the policy context well, are consistent with the goals and objectives and Policy objectives, implement prospective students firmly and strictly on policy rules, and supervise Zoning System policies following student recruitment technical guidelines and SOP, but the results are optimal, 3) The disposition as policy implementers has not seen what to do, can do these policies and have the commitment to implement student recruitment policies for optimal system zoning systems, 4) Social, economic and political conditions have influenced policy policies, 5) The zoning of system policy implementation has a positive impact on service policies and the quality of education services. This research concludes that Public Senior High School 2 Ciamis has implemented a zoning system policy, but it has yet to be optimal.